Inhibition of immune pathway-initiating hemolymph protease-14 by Manduca sexta serpin-12, a conserved mechanism for the regulation of melanization and Toll activation in insects - Wang, Yang (Insect Biochem Mol Biol, 2019)
A network of serine proteases (SPs) and their non-catalytic homologs (SPHs) activates prophenoloxidase (proPO), Toll pathway, and other insect immune responses. However, integration and conservation of the network and its control mechanisms have not yet been fully understood. Here we present evidence that these responses are initiated through a conserved serine protease and negatively regulated by serpins in two species, Manduca sexta and Anopheles gambiae. We have shown that M. sexta serpin-12 reduces the proteolytic activation of HP6, HP8, proPO activating proteases (PAPs), SPHs, and POs in larval hemolymph, and we hypothesized that these effects are due to the inhibition of the immune pathway-initiating protease HP14. To test whether these changes are due to HP14 inhibition, we isolated a covalent complex of HP14 with serpin-12 from plasma using polyclonal antibodies against the HP14 protease domain or against serpin-12, and confirmed formation of the complex by 2D-electrophoresis, immunoblotting, and mass spectrometry. Upon recognition of bacterial peptidoglycans or fungal β-1,3-glucan, the zymogen proHP14 became active HP14, which formed an SDS-stable complex with serpin-12 in vitro. Activation of proHP21 by HP14 was suppressed by serpin-12, consistent with the decrease in steps downstream of HP21, proteolytic activation of proPAP3, proSPH1/2 and proPO in hemolymph. Guided by the results of phylogenetic analysis, we cloned and expressed A. gambiae proSP217 (an ortholog of HP14) and core domains of A. gambiae serpin-11 and -17. The recombinant SP217 zymogen became active during expression, with cleavage between Tyr(394) and Ile(395). Both MsHP14 and AgSP217 cleaved MsSerpin-12 and AgSRPN11 at Leu*Ser (P1*P1’) and formed complexes in vitro. ProPO activation in M. sexta plasma increased after recombinant AgSP217 had been added, indicating that it may function in a similar manner as the endogenous initiating protease HP14. Based on these data, we propose that inhibition of an initiating modular protease by a serpin may be a common mechanism in holometabolous insects to regulate proPO activation and other protease-induced immune responses.